Meter Daya 1 Fasa Dengan Proteksi Over Voltage Dan Under Voltage berbasis Internet of Things (IoT) - Endro Wahjono; Mochammad Machmud Rifadil; Ony Asrarul Qudsi; Muhammad Nur Sururi (INOVTEK - Seri Elektro, 2020)
This research discusses about design and implementation of the power meters which are equipped with over or under voltage relays at 1 phase load based on internet of things (IoT). The power meters use power sensors that can detect active power values (P), apparent power (S), voltage (V), current (I), power factor (PF), frequency, energy, and total harmonic distortion (THD). Data on the power meter will be sent and stored in the database. Data on the power meters can also be monitored remotely via smartphones and personal computers using internet media. The power meters are equipped with indicators for over voltage, normal and under voltage conditions. This power meter is also equipped with a relay to disconnect the power at the load when there is interference with over voltage or under voltage on the system. From the results of tests that have been carried out, the relay will cut the load when there is interference with over voltage or under voltage on the system. Based on the results of testing that has been done, the design of the power meter made in this research had an average error of 0.0562% for resistive load and has the largest data readout error is 9.255% for non-linear load.